PERSPECTIVES OF THE BIOFUEL CONSUMPTION IN CIVIL AVIATION - S. A. Rybkin; S. A. Popova (Научный вестник МГТУ ГА, 2016)
This article presents the results of research on the practical experience of biofuel consumption in transport sector. Different trends and perspectives of possible consumption of biofuel are given.